Omnidirectionally stretchable, biodegradable mesh electrode with re-entrant structure for spatial-stable functional position on dynamic organs - Kim, Jaewon; Kim, Kyung Su; Kim, Seungbin; Lee, Yong-seok; Koo, Jahyun (Frontiers in Nanotechnology, 2025)
The electrode, interfacing with soft tissue, is vulnerable to mechanical failure caused by dynamic organ motions such as cardiac activity, respiration, and digestion. Mechanical mismatch can also lead to tissue damage and sensor displacement. However, existing strategies for conformal integration often fall short of preserving mechanical compliance across large-area, multi-electrode arrays. Most internal organs undergo complex, anisotropic volumetric expansion from physiological activity, requiring implanted systems that can withstand multidirectional strains without inducing stress concentration. Conventional elastomers and mesh-structured electrodes typically exhibit a positive Poisson’s ratio, which hinders multidirectional uniform stretching and results in mechanical mismatch at the tissue–electrode interface. This mismatch not only increases local mechanical load but also leads to electrode displacement. In this study, we propose a conformal electrode design that incorporates a re-entrant geometry into a stretchable and biodegradable polyurethane substrate. Mechanical testing confirmed that this geometry enhances stretchability and reduces the effective modulus of the electrode by approximately 64%. Furthermore, the device maintained electrical stability under cyclic deformation and preserved its structural integrity under dynamic, organ-mimicking volumetric expansion. This mechanical and electrical robustness highlights the potential of the proposed design for long-term integration into implantable electrode arrays for physiological monitoring and disease diagnosis on dynamic three-dimensional organ motion.